Antioxidant Mechanisms of the Protective Action of Selenase in Experimental Chronic Generalized Periodontitis - Salnykov, V. I.; Belenichev, I. F.; Makyeyeva, L. V.; Skoryna, D. Yu.; Oksenych, V.; Kamyshnyi, A.; Сальников, В. І.; Бєленічев, Ігор Федорович; Макєєва, Людмила Валеріївна; Скорина, Дмитро Юрійович (My University, 2025)
Inflammatory periodontal diseases, despite all the efforts of modern dentistry, remain an important predictor of tooth loss worldwide. Oxidative stress plays a crucial role in the pathogenesis of periodontitis, making the use of antioxidants an attractive option for its treatment. Our attention was drawn to the selenium compound Selenase as an antioxidant therapeutic agent. In this study, we modeled a calcium-deficient prooxidant chronic generalized periodontitis (CGP) model in white non-linear rats. Then, after 14 days, Selenase (50 μg/kg) and Mexidol (250 mg/kg) were administered intragastrically. Blood samples from the animals were analyzed using ELISA and biochemical methods to determine Cu-Zn SOD, nitrotyrosine, GPX-4, iNOS, NOx, GSH, and GSSG levels. The CGP model led to the typical clinical signs of periodontitis, including hyperemia, edema, gingival pocket formation, bleeding, tooth mobility, as well as an increase in molecular– biochemical markers of nitrosative stress and a reduction of endogenous antioxidants in the blood. Selenase resulted in a decrease in the clinical manifestations of CGP, reduced iNOS, nitrotyrosine, and NOx levels, and an increase in Cu-Zn SOD and GPX-4 compared to the control group (p < 0.05). Mexidol had a less pronounced effect on these markers compared to Selenase (p < 0.05).
Keywords: chronic generalized periodontitis; Selenase; nitrosative stress; antioxidant system